Gendering Outcomes: Different Paths, Similar Outcomes: An Analysis of Cross-Generational Biographical Consequences of Activism in Feminist Spaces - Bonu, Giada (PARTECIPAZIONE E CONFLITTO, 2021)
This article analyzes different paths leading to similar outcomes across three age-cohorts of activists in three feminist spaces in Italy. It addresses three challenges in the literature on biographical outcomes. First, it brings forward the methodological problem of recognizing crossing-points, which define a before-and-after in the activist's life course. Second, it improves the ways in which gender and sexuality are discussed in terms of biographical outcomes. Third, this empirical study elaborates the time in movement and the generational aspects of biographical outcomes, emphasizing the radical challenge of the younger cohorts and the long-term effects on the older cohort. This article suggests that only by deep case study, which incorporates different feminist spaces, we are able to better understand the gendered and generational biographical outcomes of feminist movements. These results can also be insightful for the analysis of other types of collective action outcomes.